Azas Keterbukaan Bagi Pelayanan Internet Berbayar di Lingkungan Kota dan Kabupaten Bogor Terhadap Provider - Riki Nova Nugraha -; Endeh Suhartini; Nurwati (JURNAL ILMIAH LIVING LAW, 2025)
This research is an empirical legal research. Empirical legal research, namely legal research conducted by collecting data from primary data or data obtained directly from research subjects, which is carried out either through observation or direct interviews. Based on the research results, it is known that the form of responsibility given by the Provider (ISP) for internet network quality disturbances experienced by customers (consumers) varies. The legal protection given to consumers due to disruption to the quality of the internet network according to Law Number 8 of 1999 concerning Consumer Protection is that consumers have the right to claim compensation from the ISP, unless the ISP can prove that the loss was not caused by their mistakes and/or negligence Completion of compensation losses can be implemented through court proceedings or out of court, such as through conciliation, mediation, or arbitration as well as through an institution tasked with resolving disputes between consumers and business actors, namely the Consumer Dispute Settlement Agency (BPSK).